2020
DOI: 10.1177/1045389x20948608
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of a porous rotor integrated with regular patterns of circumferentially distributed functionally graded piezoelectric patches on inner and outer surfaces

Abstract: This article studies dynamic characteristics of a novel porous cylindrical hollow rotor based on the first-order shear deformation theory and Hamilton’s principle. The proposed model is made from a core including aluminum with porosity integrated with an arrangement of functionally graded piezoelectric patches placed on its inner and outer surfaces with a customized circumferential orientation. The piezoelectric patches are subjected to applied electric potential as sensor and actuator. The kinematic relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…It is found that the presence of cracks weakened oil film forces of the bearing-rotor system at high speeds, the clearance ratio had a greater effect on internal and external oil film vorticity, and the rotor operating stability can be improved by increasing the impeller eccentricity. Irani-Rahaghi et al 42 and Heidari et al [43][44][45][46] studied free vibration of functionally sandwich cylindrical shells integrated with a piezoelectric layer.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the presence of cracks weakened oil film forces of the bearing-rotor system at high speeds, the clearance ratio had a greater effect on internal and external oil film vorticity, and the rotor operating stability can be improved by increasing the impeller eccentricity. Irani-Rahaghi et al 42 and Heidari et al [43][44][45][46] studied free vibration of functionally sandwich cylindrical shells integrated with a piezoelectric layer.…”
Section: Introductionmentioning
confidence: 99%
“…Tere are various solutions for the free vibration analysis of the RCS; for example, some scholars used Galerkin's method to analyze the free vibration characteristics of the RCS [1][2][3][4][5], and the diferential quadrature method was also used to study the traveling wave properties of the free vibration for the RCS [6][7][8][9][10][11]. In addition, Ritz method was relatively simple in calculation process and could maintain high accuracy, so it was widely used in the research of vibration characteristics of RCS.…”
Section: Introductionmentioning
confidence: 99%